A high-performance two-component hybrid adhesive for bonding and sealing new energy battery packs
Patent Information
- Application Number
- CN202510792183.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-13
- Publication Date
- 2026-10-20
AI Technical Summary
但该专利所述杂化胶粘接强度低,无法满足汽车电池包结构粘接强度要求
[0024]本发明专利中,通过A组分中硅烷封端聚氨酯和B组分环氧树脂的比例精确设计可以获得高强度高韧性的双组份杂化胶,使SPUR-EP形成连续均匀的杂化互穿网络“海-岛”结构,提高双组份杂化胶产品的力学性能,使产品的强度-弹性取得最佳平衡;并通过对树脂和助剂种类的选择及复配,明显改善产品对多种基材附着力、产品耐湿热老化性能。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical adhesives, and in particular to a high-performance two-component hybrid adhesive for bonding and sealing new energy battery packs. Background Technology
[0002] The global new energy vehicle market continues to grow, with penetration rates steadily increasing. Currently, China's new energy vehicle market is experiencing rapid development and is the world's largest. For ten consecutive years, China has been the world's largest producer and seller of new energy vehicles, with total sales exceeding ten million units in 2024 and a penetration rate reaching 40%. New energy vehicles are a new industry strongly advocated, supported, and encouraged by the government. With the continued increase in market acceptance and the ongoing upgrades in vehicle intelligence, the scale of the new energy vehicle and new energy battery industries will continue to grow, indicating a very promising future for my country's new energy vehicle market.
[0003] The development trend of the new energy battery industry is towards integration and lightweighting, with the increasing use of lightweight materials such as aluminum-magnesium alloys, high-strength steel, and composite materials. Currently, most existing new energy battery packs use polyurethane structural adhesives for bonding, and single-component silicone or single-component MS silane-modified polyether adhesives for sealing. Single-component silicone and MS silane-modified polyether adhesives suffer from disadvantages such as low bonding strength (1-3 MPa) and slow curing speed; airtightness testing can only be performed 24 hours after bonding the battery pack casing, resulting in low production efficiency. Two-component high-strength polyurethane structural adhesives, on the other hand, have disadvantages such as low elongation at break (<100%), low high-temperature strength, high low-temperature modulus, and poor toughness, making it difficult to meet the requirements of current new energy battery applications across a wide temperature range.
[0004] Therefore, there is a need to develop an adhesive for bonding and sealing new energy battery packs. This adhesive should possess broad applicability to various substrates, high bonding strength, high elongation at break, excellent high and low temperature performance, and excellent aging performance, ensuring the stability, durability, and safety of battery pack bonding. It should meet the requirements of the new energy battery industry for high bonding strength, good toughness, and good vibration resistance. Using high-performance structural adhesives for bonding and sealing in new energy battery pack assembly improves the structural stability and safety performance of the battery pack. It can be used for bonding metal-to-metal connections within new energy battery packs, as well as for bonding various composite materials to metals.
[0005] Patent CN 109880569 B discloses an epoxy resin-modified MS sealant, which improves the strength of the MS sealant by adding epoxy resin. However, this patent does not elaborate on the method of EP reinforcement of MS, does not verify the product's aging performance, and does not conduct further performance verification for practical applications.
[0006] Patent CN 116162432 discloses a high-temperature resistant two-component modified silane adhesive and its application, which improves temperature resistance by adding epoxy resin and metal silicide. In this patent, the epoxy resin and silane-modified resin exist in different components, and are simply physically blended to achieve an initial balance of elastic strength; however, it does not describe whether the two chemical systems are chemically cross-linked, nor does it conduct further in-depth research on the product's resistance to high and low temperature shock and damp heat aging.
[0007] Patent CN 118496261 A discloses a hybrid adhesive curing agent, a two-component hybrid adhesive for new energy batteries, and its preparation method. The synthesis of the hybrid curing agent produces a cross-linking dual-curing effect, improving the hybrid adhesive's resistance to thermal shock. However, the synthesis process of this patented hybrid adhesive curing agent is cumbersome: it requires an ice-water bath at 0-5℃ and a raw material drop-addition step; furthermore, the production process of component A of the adhesive requires high-temperature vacuum dehydration, making the process complex, and the product's storage stability has not been further verified.
[0008] Patent CN 119331556 A discloses a two-component hybrid adhesive, its preparation method, and its application. By introducing a specific coupling agent, the mechanical properties and aging resistance of the two-component hybrid adhesive are improved. However, the hybrid adhesive described in this patent has low adhesive strength, which cannot meet the adhesive strength requirements of automotive battery pack structures. Summary of the Invention
[0009] Purpose of the invention: The purpose of this invention is to provide a high-performance two-component hybrid adhesive for bonding and sealing new energy battery packs. It is expected that the product will have excellent bonding performance to different types of substrates such as aluminum, electrophoretic painted steel, powder-coated steel, and composite materials without special treatment of the substrate. It also has excellent resistance to high and low temperatures and high temperature and high humidity aging, excellent fatigue vibration resistance and dynamic environmental tolerance, and can meet various dynamic and static loads during vehicle operation, as well as deformation at different temperatures.
[0010] The technical solution of the present invention:
[0011] This invention provides a high-performance two-component hybrid adhesive for bonding and sealing new energy battery packs. The two-component hybrid adhesive includes component A and component B. Component A includes a silane-terminated polymer, an epoxy curing agent, a silane coupling agent, and additives. Component B includes an epoxy resin, a silane-terminated polymer curing agent, and additives.
[0012] In some embodiments, the silane-terminated polymer is one or more combinations of diekoxy or trialkoxy-terminated silane-terminated polyurethanes (SPURs); specifically, the SPUR is selected from Momentive's SPUR 1015, SPUR 1020, SPUR 1050, SPUR 1060, SPUR 1070, SPUR 3030, SPUR 3040, or more.
[0013] In some embodiments, the epoxy curing agent is selected from at least one of aliphatic amines, aromatic amines, alicyclic amines, modified amines, acid anhydrides, low molecular weight polyamides, and latent amines; specifically, the epoxy curing agent is selected from one or more combinations of (1,3-cyclohexanedimethylamine) alicyclic amines, diethylenetriamine, isophorone diamine, and polyether amines.
[0014] In some embodiments, the silane coupling agent is selected from one or more combinations of vinyltrimethoxysilane, vinyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, bis(trimethoxysilylpropyl)amine, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
[0015] Furthermore, the silane coupling agent is selected from one or more combinations of γ-aminopropyltrimethoxysilane and bis(trimethoxysilylpropyl)aminesilane.
[0016] Furthermore, the silane coupling agent is a mixture of γ-aminopropyltrimethoxysilane and bis(trimethoxysilylpropyl)amine silane, and the weight ratio of γ-aminopropyltrimethoxysilane to bis(trimethoxysilylpropyl)amine silane is 3:1 to 1:3.
[0017] In some embodiments, the additive is selected from one or more combinations of fillers, diluents, flame retardants, pigments, antisettling agents, defoamers, dispersants, antioxidants, and leveling agents.
[0018] In some embodiments, the epoxy resin is selected from one or more of E41 type bisphenol A diglycidyl ether epoxy resin, E44 type bisphenol A diglycidyl ether epoxy resin, E51 type bisphenol A diglycidyl ether epoxy resin, E54 type bisphenol A diglycidyl ether epoxy resin, cashew phenol modified glycidyl ether epoxy resin, bisphenol F epoxy resin, and phenolic epoxy resin; preferably, the epoxy resin in component B is one or more combinations of E44 type bisphenol A diglycidyl ether epoxy resin and bisphenol F epoxy resin.
[0019] In some embodiments, component B further includes an epoxy toughening agent, which is a thermoplastic elastomer epoxy toughening agent; further, the epoxy toughening agent is selected from one or more combinations of QS-BE, QS-BC, QS-EC, and QS-030N.
[0020] In some embodiments, the SPUR curing agent is selected from one or more combinations of dibutyltin dilaurate, stannous octoate, dibutyltin diacetate, potassium isooctanoate, zinc isooctanoate, and bismuth isooctanoate.
[0021] In some embodiments, by weight, component A comprises 20-95 parts silane-terminated polyurethane, 3-10 parts epoxy curing agent, 1-5 parts silane coupling agent, and 0.1-10 parts additives; and component B comprises 40-100 parts epoxy resin, 0-40 parts epoxy toughening agent, 0.5-5 parts SPUR curing agent, and 0.1-10 parts additives.
[0022] In some embodiments, the weight ratio of component A to component B is 1-4:1.
[0023] Beneficial effects:
[0024] In this invention patent, a high-strength and high-toughness two-component hybrid adhesive can be obtained by precisely designing the ratio of silane-terminated polyurethane in component A and epoxy resin in component B. This allows SPUR-EP to form a continuous and uniform hybrid interpenetrating network "sea-island" structure, improving the mechanical properties of the two-component hybrid adhesive product and achieving the best balance between strength and elasticity. Furthermore, by selecting and compounding the types of resins and additives, the adhesion of the product to various substrates and its resistance to humid heat aging are significantly improved. Detailed Implementation
[0025] The present invention will be described below with reference to specific embodiments. It should be noted that the following embodiments are examples of the present invention and are used only to illustrate the invention, not to limit it. Other combinations and various modifications within the scope of the present invention can be made without departing from its spirit or scope.
[0026] Unless otherwise specified, all chemical reagents used in this invention are commercially available analytical grade reagents.
[0027] Example 1
[0028] This embodiment provides a high-performance two-component hybrid adhesive for bonding and sealing new energy battery packs.
[0029] The two-component hybrid adhesive comprises component A and component B. By weight, component A comprises 91 parts of silane-terminated polyurethane (Momentive SPUR 1015), 5 parts of epoxy curing agent (diethylenetriamine), 1 part of silane coupling agent (γ-glycidyl etheroxypropyltrimethoxysilane), 1 part of antioxidant (antioxidant 1010), 1 part of pigment (Permanent Yellow PY83), and 1 part of filler (fumed silica TS720). Component B comprises 97 parts of epoxy resin (E44 type bisphenol A diglycidyl ether epoxy resin), 1 part of SPUR curing agent (Evonik DABCO), 1 part of pigment (phthalocyanine blue BGS), and 1 part of filler (fumed silica TS720).
[0030] The weight ratio of component A to component B is 1:1.
[0031] Example 2
[0032] The basic structure is the same as in Example 1, except that the weight ratio of component A to component B is 2:1.
[0033] Example 3
[0034] The basic structure is the same as in Example 1, except that the weight ratio of component A to component B is 4:1.
[0035] Example 4
[0036] The basic formula is the same as in Example 1, except that the silane coupling agent in component A is γ-aminopropyltrimethoxysilane instead of γ-glycidoxypropyltrimethoxysilane in Example 1.
[0037] Example 5
[0038] The two-component hybrid adhesive comprises component A and component B. By weight, component A comprises 91 parts of silane-terminated polyurethane (Momentive SPUR 1015), 5 parts of epoxy curing agent (diethylenetriamine), 1 part of silane coupling agent (γ-glycidoxypropyltrimethoxysilane), 1 part of antioxidant (antioxidant 1010), 1 part of pigment (Permanent Yellow PY83), and 1 part of filler (fumed silica TS720). Component B comprises 67 parts of epoxy resin (E44 type bisphenol A diglycidyl ether epoxy resin), 30 parts of epoxy toughening agent (QS-BE), 1 part of SPUR curing agent (Evonik DABCO), 1 part of pigment (phthalocyanine blue BGS), and 1 part of filler (fumed silica TS720).
[0039] Example 6
[0040] The process is basically the same as in Example 5, except that the epoxy toughening agent QS-EC is used instead of QS-BE in Example 5.
[0041] Example 7
[0042] The process is basically the same as in Example 5, except that 91 parts of silane-terminated polyurethane SPUR 3030 are used instead of SPUR 1015 in Example 5.
[0043] Example 8
[0044] The two-component hybrid adhesive comprises component A and component B. By weight, component A comprises 60 parts silane-terminated polyurethane (Momentive SPUR 1015), 31 parts silane-terminated polyurethane (Momentive SPUR 3030), 5 parts epoxy curing agent (diethylenetriamine), 1 part silane coupling agent (γ-aminopropyltrimethoxysilane), 2 parts silane coupling agent (bis(trimethoxysilylpropyl)amine), 1 part antioxidant (antioxidant 1010), 1 part pigment (Permanent Yellow PY83), and 1 part filler (precipitated silica TS720). Component B comprises 67 parts epoxy resin (E44 type bisphenol A diglycidyl ether epoxy resin), 30 parts epoxy toughening agent (QS-BE), 1 part SPUR curing agent (Evonik DABCO), 1 part pigment (phthalocyanine blue BGS), and 1 part filler (precipitated silica TS720).
[0045] Comparative Example 1
[0046] This comparative example provides a two-component adhesive.
[0047] The two-component adhesive comprises component A and component B. By weight, component A comprises 91 parts of silane-terminated polyurethane (Momentive SPUR 1015), 1 part of silane coupling agent (γ-glycidoxypropyltrimethoxysilane), 1 part of antioxidant (antioxidant 1010), 1 part of pigment (Permanent Yellow PY83), and 1 part of filler (precipitated silica TS720). Component B comprises 67 parts of polyether polyol (PPG-4000), 30 parts of heavy calcium carbonate (1250 mesh), 1 part of SPUR curing agent (Evonik DABCO), 1 part of pigment (phthalocyanine blue BGS), and 1 part of filler (precipitated silica TS720).
[0048] The weight ratio of component A to component B is 1:1.
[0049] Comparative Example 2
[0050] This comparative example provides a two-component adhesive.
[0051] The two-component hybrid adhesive comprises component A and component B. By weight, component A comprises 31 parts polyetheramine (Evonik D230), 60 parts heavy calcium carbonate (1250 mesh), 5 parts epoxy curing agent (diethylenetriamine), 1 part silane coupling agent (γ-glycidoxypropyltrimethoxysilane), 1 part antioxidant (antioxidant 1010), 1 part pigment (permanent yellow PY83), and 1 part filler (fumed silica TS720). Component B comprises 97 parts epoxy resin (E44 type bisphenol A diglycidyl ether epoxy resin), 1 part pigment (phthalocyanine blue BGS), and 1 part filler (fumed silica TS720).
[0052] The weight ratio of component A to component B is 1:1.
[0053] Performance testing
[0054] 1. Tensile strength / elongation at break test
[0055] Test standard: Refer to GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber;
[0056] Testing equipment: dumbbell-shaped mold + universal tensile testing machine;
[0057] Test method: Apply adhesive to the specimen in a PTFE mold conforming to the dimensions of dumbbell type 1 of GB / T 528 and smooth it. Cure the prepared tensile specimen at 23±2℃ for 7 days; clamp the cured tensile specimen on the tensile fixture of a universal tensile testing machine, and test the tensile strength and elongation at break at a testing speed of 100 mm / min.
[0058] 2. Hardness test
[0059] Test standard: GB / T 531-2008 Test method for indentation hardness of vulcanized rubber or thermoplastic rubber;
[0060] Testing equipment: LX-A Shore hardness tester;
[0061] Test method: Apply adhesive to the sample in a 90mm×50mm×6mm PTFE plate mold and smooth it. Cur the prepared hardness sample at 23±2℃ for 7 days. Place the cured sample in the positioning disk of a Shore A hardness tester, press the pointer of the hardness tester into the sample at a speed of less than 3.2mm / s, hold for 3 seconds, and then take the reading.
[0062] 3. Tensile shear strength test
[0063] Test standard: Refer to GB / T 7124-2008 Determination of tensile shear strength of adhesives;
[0064] Testing equipment: Universal tensile testing machine;
[0065] Test method: First, wipe the surface of the substrate with anhydrous ethanol, then apply adhesive to the substrate, controlling the adhesive area to be 25.0mm × 12.5mm. Press the adhesive layer to control the thickness to be 0.2mm, and fix the bonding parts with clips. Cure the shear sample at 23±2℃ for 7 days. The cured shear sample is clamped on the shear fixture of a universal tensile testing machine. The tensile testing speed is 5mm / min, and the tensile shear strength is tested.
[0066] The test results are shown below.
[0067] Table 1
[0068]
[0069] Comparison of Examples 1-3 revealed that when the A / B component ratio is 1:1, the product exhibits both high tensile strength and elongation at break (≥300%), and a shear strength >7MPa when bonded to the aluminum substrate. This means that under the optimal two-phase component ratio (1:1), the SPUR and EP system can form a continuous and uniform interpenetrating network "sea-island" structure, achieving the best balance between strength and elasticity, resulting in superior mechanical properties. The designed two-component hybrid adhesive product can meet the integrated functional requirements of bonding and sealing, improving the reliability of bonding strength and the stability of sealing for new energy battery packs.
[0070] Table 2
[0071]
[0072]
[0073] Comparative Examples 1-2 illustrate that it is difficult for a single SPUR or epoxy product to simultaneously achieve high tensile strength and elongation at break. Furthermore, single products generally exhibit low shear strength and poor aging resistance. Two-component hybrid adhesives, through precise design of the ratio of SPUR resin in component A and epoxy in component B, and a dual-curing system, can achieve products with high strength and high elongation. These adhesives are suitable for bonding various substrates, possess high bond strength, and exhibit excellent resistance to damp heat and high / low temperature impact aging.
[0074] Compared to the conventional method of adding modified fillers to improve the compatibility of two systems, Examples 5-6, through the toughening modification of component B epoxy, not only improved the compatibility of the epoxy and SPUR systems but also enhanced the product's resistance to high and low temperature impacts. Secondly, the formulation system does not require the addition of modified fillers, optimizing the production process by eliminating the need for high-temperature dehydration and improving production efficiency; it also reduces the product density, meeting the trend of lightweight battery packs. Example 7, through the blending of different resins, further improves the product's adhesive strength. The product of Example 7 exhibits excellent aging resistance, with a retention rate of ≥90% for both double 85 / 1000h and high and low temperature (-40~85℃) impact aging strength.
[0075] Table 3
[0076]
[0077] Example 8 improves the adhesion of the product to various materials and further enhances its adhesive strength by introducing and compounding a silane coupling agent with a special structure containing multiple siloxane groups. The introduction of a functional aminosilane coupling agent in component A forms an effective chemical crosslinking network between the SPUR resin and epoxy resin, improving the mechanical properties and aging resistance under high humidity and heat. The product retains ≥90% of its shear strength after 85 / 1000h aging, meeting the industry standards for adhesives used in new energy vehicle battery packs.
[0078] The two-component hybrid adhesive provided in Example 8 exhibits high adhesive strength and excellent aging performance for various materials used in new energy vehicles. Example 8 shows an adhesive strength >10 MPa for metal materials in new energy vehicles and >8 MPa for metal-composite PP / GF materials. The compounding and synergistic effect of the coupling agent results in excellent adhesive performance, high adhesive strength, and high elongation at break. It also possesses excellent resistance to high temperature and high / low temperature impact aging.
[0079] This invention can also be implemented in various other ways. Without departing from the spirit and essence of this invention, those skilled in the art can make various corresponding changes and modifications according to this invention, but these corresponding changes and modifications should all fall within the protection scope of the appended claims.
Claims
1. A high-performance two-component hybrid adhesive for bonding and sealing new energy battery packs, wherein the two-component hybrid adhesive comprises component A and component B; characterized in that, Component A includes a silane-terminated polymer, an epoxy curing agent, a silane coupling agent, and additives; Component B includes an epoxy resin, a silane-terminated polymer curing agent, and additives.
2. The two-component hybrid adhesive according to claim 1, characterized in that, The silane-terminated polymer is selected from one or more of Momentive's SPUR 1015, SPUR 1020, SPUR 1050, SPUR 1060, SPUR 1070, SPUR 3030, and SPUR 3040.
3. The two-component hybrid adhesive according to claim 2, characterized in that, The silane-terminated polymer is selected from Momentive's SPUR 1015, SPUR 1060, and SPUR 3030.
4. The two-component hybrid adhesive according to claim 1, characterized in that, The silane coupling agent is selected from one or more combinations of vinyltrimethoxysilane, vinyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, bis(trimethoxysilylpropyl)amine, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.
5. The two-component hybrid adhesive according to claim 4, characterized in that, The silane coupling agent is a mixture of γ-aminopropyltrimethoxysilane and bis(trimethoxysilylpropyl)aminesilane.
6. The two-component hybrid adhesive according to claim 1, characterized in that, The epoxy resin is selected from one or more of the following: E41 type bisphenol A diglycidyl ether epoxy resin, E44 type bisphenol A diglycidyl ether epoxy resin, E51 type bisphenol A diglycidyl ether epoxy resin, E54 type bisphenol A diglycidyl ether epoxy resin, cashew phenol modified glycidyl ether epoxy resin, bisphenol F epoxy resin, and phenolic epoxy resin. Preferably, the epoxy resin in component B is one or more combinations of E44 type bisphenol A diglycidyl ether epoxy resin and bisphenol F epoxy resin.
7. The two-component hybrid adhesive according to claim 1, characterized in that, Component B further includes an epoxy toughening agent, which is a thermoplastic elastomer-based epoxy toughening agent.
8. The two-component hybrid adhesive according to claim 1, characterized in that, The silane-terminated polymer curing agent is selected from one or more combinations of dibutyltin dilaurate, stannous octoate, dibutyltin diacetate, potassium isooctanoate, zinc isooctanoate, and bismuth isooctanoate.
9. The two-component hybrid adhesive according to claim 7, characterized in that, By weight, component A comprises 20-95 parts of silane-terminated polymer, 3-10 parts of epoxy curing agent, 1-10 parts of silane coupling agent, and 0.1-10 parts of additives; component B comprises 40-100 parts of epoxy resin, 0-40 parts of epoxy toughening agent, 0.5-5 parts of silane-terminated polymer curing agent, and 0.1-10 parts of additives.
10. The two-component hybrid adhesive according to claim 1, characterized in that, The weight ratio of component A to component B is 1-4:1.
Citation Information
Patent Citations
An epoxy resin modified MS sealant
CN109880569B
Two-component hybrid gel as well as preparation method and application thereof
CN119331556A